Sulfur oxidation on Pt(355): It is the steps! - Streber, Regine; Papp, Christian; Lorenz, Michael Peter Andreas; Bayer, Andreas; Denecke, Reinhard; Steinrück, Hans-Peter (Angewandte Chemie International Edition, 2009)
Steps in the right direction: The role of steps in the removal of sulfur from a Pt model catalyst via metastable SO and SO species, was demonstrated by in situ high-resolution X-ray photoelectron spectroscopy. From isothermal experiments the activation energy of the rate-determining step was deduced to be 34 kJmol. © 2009 Wiley-VCH Verlag GmbH &. Co. KGaA.